Factors Affecting Consumer’s Purchase Decision on TikTok Live Shopping, with Perceived Value as the Mediating Variable in Jakarta - Annisa Putri Shafira; Natatsa Indhagelista; Regita Esmeralda; Minsani Mariani (ITB AAS Indonesia Surakarta, 2024)
This study is aimed to knowing the effect of the role of influencer, promotion, perceived scarcity, and perceived value on Tik Tok live shopping on purchase decisions. This study uses descriptive quantitative method because the data is presented in numerical and descriptive form. The sample is determined as many 254 male and female users of the TikTok application in Jakarta. In this study, data are collected using a questionnaire method as primary data. The data analysis in this research uses descriptive analysis as an analysis tool in data processing. Beside that, this study uses multiple linear regression methods to obtain the effect of the independent variables on the dependent variable. Based on the analysis result, it can be concluded that that three key factors have a significant impact on purchase decisions: promotion, scarcity, and perceived value on TikTok Live Shopping. The future research directions are expected to provide to a deeper understanding of purchase decisions on TikTok Live Shopping, uncover new insights, and inform marketing strategies within this rapidly evolving domain.